Monitoramento da qualidade da areia de moldagem em uma fundiçã o de autopeças de ferro fundido - Claro, Fernando Antonio Elias; Costa, Antonio Fernando Branco [UNESP]; Medrano, Julio Henrique Pimentel (My University, 2010)
The purpose of this paper is to describe the application of a control chart for means with double sampling to monitor the green sand compactability in a major foundry where iron castings for the automotive segment are produced. Compactability measurements carried out at the end of consecutive sand mixing cycles have indicated that the variable observations fit to an autocorrelated process. To set the control limits of the control chart introduced in this study the serial dependence was taken into account and the chart properties were obtained from closed-form expressions. The control chart design and statistical power allow the quick detection of process disturbances without any extra sampling effort. Due to these features, the green sand compactability can be consistently monitored, preventing the occurrence of defective sand molds and castings. Copyright © (2010) by Associação Brasileira de Metalurgia Materiais e Mineração (ABM).
Molding sand quality monitoring for autoparts production in a cast iron foundry
Keywords: Autocorrelation; Control chart; Molding sand; Quality